Activated carbon and halloysite nanotubes membrane for CO2 and CH4 separation. Issue 1 (April 2021) - Gunasakaran, A; Jafa, J; Saalah, S; Sipaut, C S; Yusof, N; Aziz, F; Ismail, A F; Bilad, M R; Yahya, N Y; Ismail, N M
Abstract: In this study, mixed matrix membranes (MMMs) were prepared where activated carbon and halloysite nanotubes with a loading of 1 wt% is incorporated into the polysulfone membrane, and the performance of each membrane was investigated. The morphological properties, mechanical strength and their correlations with the gas separation performance for CO2 and CH4 for halloysite-mixed matrix membrane (MMMs-HNT) and activated carbon-mixed matrix membrane (MMMs-AC) was studied by using Scanning Electron Microscopy (SEM-EDX), tensile test and gas permeation test. From the characterization of MMMs, SEM shows an increase of 30.77% on the thickness of the dense layer of MMMs-HNTs compared to neat membrane and MMMs-AC. The EDX results also showed that HNTs evenly distributed in the polymeric matrix without any sign of agglomeration. Elongation at the break for MMMs-HNTs also decreases to 11.38%. The gas separation performance for MMMs-HNTs increased by about 55.43% compared to MMMs-AC at 2 bar. Furthermore, MMMs-HNTs also showed in increase in the selectivity of membrane towards CO2 and CH4 from 0.82 to 15.83 at 2 bar. In conclusion, the addition of 1 wt% of HNTs into PSF polymeric matrix showed a better permeance of CO2 and a greater selectivity compared to the neat membrane and the MMMs-AC and thus is the optimum inorganic filler for the mixed matrix membrane.